PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BAJU THRIFT BUYED ID - Vadya Marshanda Budiman; Dedi Mulyadi; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of price and product quality on the decision to purchase thrift clothes at Buyed Id. The research method used is a quantitative approach by collecting data through questionnaires distributed to Buyed Id customers, especially women aged 14-30 years. The research results show that price and product quality have a significant effect on purchasing decisions. Affordable prices and good product quality are the main factors considered by consumers when buying thrift clothes. Data analysis was carried out using multiple regression, partial t test, simultaneous f test, and coefficient of determination. In conclusion, both price and product quality have a significant influence on consumer purchasing decisions at Buyed Id.